Pemberian Topikal Ekstrak Etanol Buah Adas (Foeniculum vulgare Mill.) Konsentrasi 50% Lebih Menurunkan Makrofag Dan Neutrofil Daripada Povidone Iodine Untuk Penyembuhan Radang Mukosa Mulut Tikus Putih Jantan - Putu Lestari Sudirman; Ni Kd. Fiora Rena Pertiwi; I G.A. Sri Pradnyani (School of Dentistry Faculty of Medicine Udayana University, 2017)
Dental procedure sometimes can cause injury to the oral mucosa either intentionally or unintentionally. Inflammation on mucosa of the mouth / stomatitis is an inflammation that occurs in the oral mucosa, usually form of a yellowish white spots. These patches can be single or multiple. Inflammation on the mucosa of the mouth can affect the mucous membranes of the inner cheek, inner lip, tongue, gums and palate in the oral cavity. This study uses an Experimental Randomized Post Test Only Control Group Design on 32 male rats that had been induced by H2O2, causing inflammation of the lower labial mucosa, Sample were divided into two treatment groups, each group of 16 rats. Control group get Povidone Iodine for 3 days, and the treatment group was given ethanol extract 50 % of fennel fruit for 3 days. On day 7 rats euthanized for taking the oral mucosal tissue and then made histology preparations with HE staining. Data were analyzed, with Shapiro-Wilk normality test and followed by independent T-test.The mean macrophages and neutrophils significantly different (p <0.05). It can be concluded that the ethanol extract of 50% fennel fruit, can reduce macrophages and neutrophils than Povidone Iodine, so the inflammatory process can be shorter and healing process more quickly.